EXPERIMENTAL STUDY OF THE SAFETY OF INDIRECT CERAMIC RESTORATIONS REMOVAL BY COMPARING THE DYNAMICS OF THERMOMETRIC INDICATORS - O.V. Pavlenko; O.M. Stupnytska; I.H. Chaikovskyi; V.V. Chamata (Український стоматологічний альманах)
Abstract. Today, porcelain laminate veneers are mainly used to optimize tooth form and position, close diastema, replace discoloured or unaesthetic composite resin restorations, restore teeth with incisal abrasions or tooth erosion, and mask or reduce tooth discoloration. They are a valid alternative to complete-coverage restorations since they avoid aggressive dental preparation, thus maintaining tooth structure. However, even such high-precision restorations have a failure rate and complications.